Systematic design processes of hypermedia engineering: a case study of SpLEA-Web - Jantan, Azrul Hazri; Sumari, Putra; Sulaiman, Shahida (2007)
Hypermedia engineering is having a rapid growth in today’s software engineering industry. Ongoing researches have proved that the efforts of designing and developing hypermedia applications is different compared to the conventional information system practices. It is not a trivial task and the development has generally been ad hoc. Hypermedia practitioners should clarify clearly the information contents structure, complex navigation links, functions and operations, and the presentation of user interface. The main objective of this paper is to present a clear structured view on the process of designing an educational web-based hypermedia application for a university’s faculty, called SpLEA-Web (Self-paced Learning with Exercising Approach Website), starting from the early design stage. We used UML-based design method called UWE (UML-based Web Engineering) for this purpose. Conceptual and navigation designs will be elaborated and reviewed clearly. Finally, some arguments and future refinements for UWE will be discussed and summarized at the end of the paper.